Continuous Signal Enhancement for Sensitive Aptamer Affinity Probe Electrophoresis Assay Using Electrokinetic Concentration - Cheow, Lih Feng (2011)
We describe an electrokinetic concentration-enhanced aptamer affinity probe electrophoresis assay to achieve highly sensitive and quantitative detection of protein targets in a microfluidic device. The key weaknesses of aptamer as a binding agent (weak binding strength/fast target dissociation) were counteracted by continuous injection of fresh sample while band-broadening phenomena were minimized due to self-focusing effects. With 30 minutes of continuous signal enhancement, we can detect 4.4 pM of human immunoglobulin E (IgE) and 9 pM of human immunodifficiency virus 1 reverse transcriptase (HIV-1 RT), which is among the lowest limit of detection (LOD) reported. IgE was detected in serum sample with LOD of 39 pM due to nonspecific interactions between aptamers and serum proteins. The method presented in this paper also has broad applicability to improve sensitivities of various other mobility shift assays.